Thirty years: Life, reading and the written word with RAE - Ana Paula Paes de Paula (RAE: Revista de Administração de Empresas, 2021)
The article is a report on the researcher’s career path and her activities in relation to RAE over the last 30 years. It presents the main works she has published, her interaction with colleagues and the importance of this path. This is a recollection whose aim is to inform and, who knows, to inspire young researchers.